Triglyceride-glucose index as a novel prognostic biomarker for coronary artery disease: evidence from a large-scale prospective cohort study - Feng, Baoyu; Zhao, Yejing; Xu, Wei; Meng, Xuyang; Li, Yi; Xia, Chenxi; Zhao, Zinan; Peng, Hongyu; Wang, Xiang (Frontiers in Endocrinology, 2025)
ObjectiveThe triglyceride-glucose (TyG) index, combining fasting glucose and triglyceride levels, has emerged as a promising biomarker for coronary artery disease (CAD). However, evidence for its long-term prognostic value in CAD remains limited and inconclusive.MethodsThis prospective cohort study was conducted at Beijing Hospital between January 2016 and December 2021, involving 23,591 patients with CAD. Based on the inclusion and exclusion criteria, a total of 11,325 CAD patients were included in the final analysis. TyG index was determined using the formula ln [fasting triglycerides (mg/dL) × fasting glucose. Eligible participants were stratified by TyG tertiles: Tertile 1 (TyG ≤ 8.39, n=3,775); Tertile 2 (8.40 ≤ TyG ≤ 8.92, n=3,776); Tertile 3 (TyG ≥ 8.93, n=3,774), with a median follow-up duration of 28 months. The primary outcomes were all-cause death and cardiovascular disease (CVD) death. The secondary outcome was major adverse cardiovascular events (MACE). Cox proportional hazards models and restricted cubic spline (RCS) analysis were applied to investigate the relationship between the TyG index and endpoints.ResultsRCS analyses showed a monotonic increase in all-cause death, CVD death, and MACE risks with higher TyG. Kaplan-Meier curves confirmed worse survival in higher TyG tertiles. Multivariable-adjusted analysis revealed continuous TyG index was an independent risk factor for all-cause death (HR = 1.22; 95% CI 1.02-1.45) and CVD death (HR = 1.61; 95% CI 1.17-2.22). Using the lowest TyG index tertile as the reference (T1), the highest tertile (T3) group exhibited a 1.34-fold risk of all-cause death (95% CI 1.04-1.72), a 1.99-fold risk of CVD death (95% CI 1.23-3.21), and a 1.17-fold higher risk of MACE (95% CI 1.00-1.37), respectively. Subgroup analyses showed the continuous TyG index was significantly associated with the risk of all-cause death in acute coronary syndrome (ACS) (HR = 1.33, 95% CI 1.01-1.74) and CVD death in chronic coronary syndrome (CCS) (HR = 1.79, 95% CI 1.16-2.78). With T1 as the reference, patients with CCS in the T3 group had a 2.15-fold higher risk of CVD death (95% CI 1.10-4.23).ConclusionThe TyG index correlates with increased all-cause death, CVD death, and MACE risks in CAD, with prognostic value in both ACS and CCS, particularly in CCS. These findings establish TyG as a robust CAD biomarker, warranting further clinical research.